Epigenetic basis of sensitization to stress, affective episodes, and stimulants: implications for illness progression and prevention. (June 2016) - Post, Robert M
Abstract : Objectives: The process of sensitization (increased responsivity) to the recurrence of stressors, affective episodes, and bouts of substance abuse that can drive illness progression in the recurrent affective disorders requires a memory of and increased reactivity to the prior exposures. A wealth of studies now supports the postulate that epigenetic mechanisms underlie both normal and pathological memory processes. Methods: We selectively reviewed the literature pertinent to the role of epigenetics in behavioral sensitization phenomena and discuss its clinical implications. Results: Epigenetics means above genetics and refers to environmental effects on the chemistry of DNA, histones (around which DNA is wound), and microRNA that change how easily genes are turned on and off. The evidence supports that sensitization to repeated stressor, affective episodes, and substance is likely based on epigenetic mechanisms and that these environmentally based processes can then become targets for prevention, early intervention, and ongoing treatment. Sensitization processes are remediable or preventable risk factors for a poor illness outcome and deserve increased clinical, public health, and research attention in the hopes of making the recurrent unipolar and bipolar affective disorders less impairing, disabling, and lethal by suicide and increased medical mortality. Conclusions: The findings that epigenetic chemical marks, which change in the most fundamental way how genes are regulated, mediate the long‐term increased responsivity to recurrent stressors, mood episodes, and bouts of substance abuse should help change how the affective disorders are conceptualized and move treatment toward earlier, more comprehensive, and sustained pharmacoprophylaxis.